PECULIAR FEATURES CONCERNING 1-ST-YEAR STUDENT ADAPTATION TO LIFE-ACTIVITY AT ENGINEERING HIGHER EDUCATIONAL INSTITUTION - V. A. Klimenko; V. V. Egorov (Наука и техника)
The paper contains an analysis of peculiar features concerning a 1-st-year student adaptation to new conditions of life-activity  on the basis of self-evaluation made by 212 persons.  In order to obtain the data a methodology for diagnostics of social and psychological adaptation developed by K.Rodgers and R.Diamond has been applied with the purpose to study such integral indices as adaptivity, emotional comfort, friendly attitude, internality, tolerance and domination symptom.